Aluminum oxide and aluminum nitride composite electrostatic chuck
By covering the aluminum oxide ceramic structural parts and installing an aluminum nitride ceramic dielectric layer on the metal base of the electrostatic chuck, the problem of the electrostatic chuck being easily eroded under plasma etching conditions is solved, and higher corrosion resistance and thermal conductivity are achieved, ensuring temperature uniformity and electrical insulation performance during semiconductor processing.
Patent Information
- Application Number
- CN202411723772.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing electrostatic chucks are easily eroded under plasma etching conditions, resulting in damage to metal bases and particle contamination, which cannot meet the needs of long-term and high-power usage.
A composite electrostatic chuck design of aluminum oxide and aluminum nitride is formed by coating the aluminum oxide ceramic structural parts on the metal base and installing an aluminum nitride ceramic dielectric layer below it, combining a heating layer and an adsorption electrode layer to form a multi-layer structure to improve corrosion resistance and thermal conductivity.
Effectively shield the corrosion of plasma on the metal base, avoid particle pollution, improve the high temperature, corrosion and thermal conductivity of the chuck, and ensure the temperature uniformity and electrical insulation performance during semiconductor processing.
Smart Images

Figure CN119560436A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the chuck field technology, in particular to a composite electrostatic chuck of aluminum oxide and aluminum nitride. Background Art
[0002] Generally speaking, semiconductor devices, flat panel display devices or solar cells can be manufactured through oxidation, deposition and etching processes. These processes are performed when the substrate is fixedly loaded on the chamber. In order to load the substrate fixedly on the chamber, mechanical methods or vacuum chuck methods are widely used. In recent years, electrostatic chucks using electrostatic force are more preferred.
[0003] Electrostatic chucks can be applied to all steps of manufacturing semiconductor devices, such as chemical vapor deposition, etching, sputtering and ion implantation. Electrostatic chucks adsorb substrates by Coulombic force and Johnson-Rahbeck force generated on the insulating layer between the electrode and the substrate.
[0004] However, under plasma etching conditions, the metal base used in the electrostatic chuck is easily corroded, mainly because the high-energy particles in the plasma bombard the surface of the metal base, causing physical and chemical changes on the metal surface. To this end, the current main approach is to oxidize or coat the surface of the metal base, but under plasma etching, the thin film coating physically attached to the metal surface cannot resist plasma erosion and cannot meet the requirements of long-term, high-power use. It is easily corroded by plasma, resulting in metal particle contamination and seriously affecting the life. Therefore, it is necessary to study a solution to the above problems. Summary of the invention
[0005] In view of this, the present invention aims at addressing the deficiencies in the prior art, and its main purpose is to provide a composite electrostatic chuck of aluminum oxide and aluminum nitride, which can effectively solve the problem that the prior electrostatic chuck is easily corroded.
[0006] To achieve the above purpose, the present invention adopts the following technical solutions:
[0007] A composite electrostatic chuck of aluminum oxide and aluminum nitride comprises a metal base, an aluminum oxide ceramic structure, an aluminum nitride ceramic dielectric layer, a heating layer and an adsorption electrode layer; the aluminum oxide ceramic structure is coated on the outside of the metal base, and the aluminum oxide ceramic structure comprises the following raw materials by weight percentage: Al2O385-90%, SiO2 2-5%, CeO2 2-5%, MgO 2-5%; the aluminum nitride ceramic dielectric layer comprises the following raw materials by weight percentage: AlN 85-90%, CeO2 2-5%, YF3 2-5%, CaF2 2-5%, Y2O3 2-5%, the aluminum nitride ceramic dielectric layer includes a first dielectric layer, a second dielectric layer and a third dielectric layer, the first dielectric layer is located at the top of the aluminum nitride ceramic dielectric layer, an adsorption electrode layer is arranged below it for providing adsorption voltage, and a second dielectric layer is arranged below the adsorption electrode layer for insulation, the heating layer is located below the second dielectric layer for temperature control of the working process, and the third dielectric layer is arranged below the heating layer for insulation shielding and connected to the lower alumina ceramic structural member.
[0008] As a preferred embodiment, the method for preparing the aluminum nitride ceramic dielectric layer comprises the following steps:
[0009] (1) Preparation of slurry: The raw materials for preparing the aluminum nitride ceramic dielectric layer are mixed in a certain proportion, wherein the components are AlN, CeO2, YF3, CaF2 and Y2O3, and the particle size is 0.2-3 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of a solvent and 0.5-2.5 parts by weight of a dispersant are added, and the mixture is put into a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15 mm, and the mixture is processed at a speed of 40-70 r / min for 12-24 hours; then 7-11 parts by weight of a binder and 4-8 parts by weight of a plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours. The ball-milled slurry is degassed for 1-2 hours to obtain a tape casting slurry with a viscosity of 5000-10000 mPa.s;
[0010] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3-0.6 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine;
[0011] (3) Punching: Use a laser punch or mechanical punch to process structural holes and positioning hole structures on the ceramic green tile;
[0012] (4) Printing and filling holes: The surface of the ceramic green tile after punching is printed with metal slurry and filled with holes using a printing and filling machine;
[0013] (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press for 10-30 minutes at 60-80° C. and 10-40 MPa to obtain a ceramic green sheet;
[0014] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, put it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it warm for 3-6 hours to obtain a ceramic debinding sheet;
[0015] (7) Sintering: The ceramic debonding sheet is placed in a high temperature sintering furnace and sintered at 1750-1850° C. for 2-4 hours to obtain a sintered ceramic plate;
[0016] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0017] As a preferred solution, the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main functions are to provide a conductive path and generate heat.
[0018] As a preferred solution, the method for preparing the alumina ceramic structural component comprises the following steps:
[0019] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, wherein the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 0.2-3μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of solvent and 0.5-2.5 parts by weight of dispersant are added, and the mixture is put into a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15mm, and processed at a speed of 40-70r / min for 12-24 hours; then 7-11 parts by weight of binder and 4-8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours to obtain a uniformly mixed granulation slurry;
[0020] (2) Granulation: The mixed granulation slurry is formed in a granulation drying tower to obtain granulation powder with a particle size of 50-100 μm, which is then sieved and batched through a vibrating screen;
[0021] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press, and maintain the pressure at 500T for 10 minutes to obtain an alumina blank;
[0022] (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging; the plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 60-80° C. and 150-200 MPa for 10-30 minutes to obtain a ceramic green ceramic structural part;
[0023] (5) Debinding: Place the green ceramic structural part on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it at this temperature for 3-6 hours to obtain a debinding ceramic structural part;
[0024] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1500-1650° C. for 2-4 hours to obtain a sintered ceramic structure;
[0025] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0026] As a preferred embodiment, the solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol and butanone.
[0027] As a preferred embodiment, the dispersant is one of castor oil, brown fish oil, polyethylene glycol, and phosphate ester.
[0028] As a preferred solution, the binder is polyvinyl butyral.
[0029] As a preferred embodiment, the plasticizer is one or more of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.
[0030] As a preferred solution, the aluminum nitride ceramic dielectric layer and the aluminum oxide ceramic structural member are welded by high-temperature solder to improve reliability.
[0031] As a preferred embodiment, the third dielectric layer is combined with the alumina ceramic structural component by high-temperature welding, and a plurality of helium holes are opened on the periphery of the surface of the first dielectric layer. The plurality of helium holes are arranged in a circle at intervals, and each helium hole penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer and the alumina ceramic structural component.
[0032] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0033] By coating the alumina ceramic structural part on the outside of the metal base, the alumina ceramic structural part has the characteristics of high temperature resistance, corrosion resistance and wear resistance, can effectively shield the erosion of the metal base by plasma, and does not produce particle pollutants to contaminate the wafer; and by setting the aluminum nitride ceramic dielectric layer, the aluminum nitride ceramic dielectric layer has excellent thermal conductivity and good temperature uniformity, so that the composite electrostatic chuck can effectively control the temperature during the semiconductor processing process, ensure the temperature uniformity of the wafer surface, and have good processing consistency, thereby improving the processing accuracy and product quality; the aluminum nitride ceramic dielectric layer has a low expansion coefficient and excellent dielectric properties, so that the composite electrostatic chuck has good thermal shock resistance, can maintain stable performance in an environment with drastic temperature changes, and reduce damage caused by thermal stress, thereby improving the efficiency of semiconductor manufacturing and product quality, and at the same time helps to extend the service life of the equipment and reduce maintenance costs; the aluminum nitride ceramic dielectric layer has a small number of 0.1mm particles and good insulation performance, so that the yield rate of the composite electrostatic chuck is greatly improved, and has good electrical insulation performance, which effectively prevents current leakage, ensures the safety and stability of the equipment, and reduces metal particle pollution.
[0034] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments: BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a three-dimensional schematic diagram of a preferred embodiment of the present invention;
[0036] Figure 2 It is a front view of a preferred embodiment of the present invention;
[0037] Figure 3 It is a front view of the heating layer in a preferred embodiment of the present invention;
[0038] Figure 4 is a front view of an adsorption electrode layer in a preferred embodiment of the present invention;
[0039] Figure 5 It is a cross-sectional view of a preferred embodiment of the present invention.
[0040] Description of the accompanying drawings:
[0041] 10. Metal base 20. Alumina ceramic structural parts
[0042] 30. Aluminum nitride ceramic dielectric layer 31. First dielectric layer
[0043] 32. Second dielectric layer 33. Third dielectric layer
[0044] 301, helium hole 40, heating layer
[0045] 41. First lead-out terminal 50. Adsorption electrode layer
[0046] 51. The second lead terminal. DETAILED DESCRIPTION
[0047] Please refer to Figures 1 to 5 As shown, it shows the specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride of the present invention, including a metal base 10, an aluminum oxide ceramic structure 20, an aluminum nitride ceramic dielectric layer 30, a heating layer 40 and an adsorption electrode layer 50.
[0048] The alumina ceramic structure 20 is coated on the outside of the metal base 10, mainly used to protect the metal base 10 and shield plasma erosion. The alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 85-90%, SiO22-5%, CeO2 2-5%, and MgO 2-5%. SiO2 promotes chemical action, viscous flow, particle rearrangement, and mass transfer to produce a liquid phase, thereby promoting diffusion, reducing the sintering temperature, and effectively accelerating the sintering process; CeO2 helps to form a low-temperature liquid phase, which is beneficial to low-temperature sintering; MgO helps to promote the generation of a low-melting point phase, increase the opportunity for particle rearrangement, and promote particle growth.
[0049] The alumina ceramic structural component 20 has the characteristics of high temperature resistance, corrosion resistance and wear resistance. The alumina ceramic structural component 20 uses high-purity raw materials and has fine particles, which ensures its high temperature resistance, corrosion resistance, wear resistance and other properties. It is not easy to generate particulate pollutants, shielding the plasma from erosion of the metal base 10, and at the same time does not generate particulate pollutants to contaminate the wafer.
[0050] Specifically, the method for preparing the alumina ceramic structure 20 includes the following steps:
[0051] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 0.2-3μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of solvent and 0.5-2.5 parts by weight of dispersant are added to a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15mm, and the mixture is processed at a speed of 40-70r / min for 12-24 hours; then 7-11 parts by weight of binder and 4-8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours to obtain a uniformly mixed granulation slurry. The solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol, and butanone. The dispersant is one of castor oil, brown fish oil, polyethylene glycol, and phosphate. The binder is polyvinyl butyral. The plasticizer is one or more of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.
[0052] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 50-100 μm, which is then sieved and batched using a vibrating screen.
[0053] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0054] (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 60-80°C and 150-200 MPa for 10-30 minutes to obtain a ceramic green ceramic structural part.
[0055] (5) Debinding: Place the ceramic raw material on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it at that temperature for 3-6 hours to obtain a ceramic debinding structure.
[0056] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1500-1650° C. for 2-4 hours to obtain a sintered ceramic structure.
[0057] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0058] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 85-90%, CeO2 2-5%, YF3 2-5%, CaF2 2-5%, Y2O3 2-5%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. AlN ceramics have excellent performance due to their high thermal conductivity, high strength, high insulation resistance and low dielectric constant (electrical insulation).
[0059] The thermal conductivity of AlN is above 320W / m·K, which makes aluminum nitride perform well in thermal conductivity, which is 10-15 times that of Al2O3 and close to the performance of beryllium oxide (BeO). This excellent thermal conductivity is essential for maintaining temperature uniformity because it can effectively and quickly conduct heat to avoid local overheating or overcooling, thereby ensuring uniform temperature distribution. Its density is 3.26g / cm3, elastic modulus is 300-310GPa, bending strength is 280-350MPa, and Mohs hardness is 8. Secondly, the electrical properties of AlN also provide support for use in high plasma power and high plasma concentration scenarios. The room temperature resistivity of pure AIN is greater than 10 14 Ω·cm, is a good insulating material with a dielectric constant of about 8.0 (1MHz) and a dielectric loss of 10 -4 (1MHz), these electrical properties ensure the stability of the AlN electrostatic chuck in a high-voltage environment, reduce the local heating problem caused by uneven current, and further promote the realization of temperature uniformity.
[0060] Compared with Al2O3, AlN is not easy to sinter and needs to add sintering aids. The sintering aids are CeO2 and YF3. The addition of CaF2, Y2O3 and CeO2 is beneficial to the densification of AlN ceramic sintering; CeO2 helps to improve the density of ceramics; CaF2 as a sintering aid not only promotes densification through liquid phase sintering, but also improves thermal conductivity by reducing oxygen impurities, which helps to improve the thermal conductivity and bending strength of AlN ceramics; Y2O3 helps to improve the density and mechanical properties, and removes oxygen impurities in aluminum nitride ceramics to improve thermal conductivity.
[0061] Specifically, the method for preparing the aluminum nitride ceramic dielectric layer 30 comprises the following steps:
[0062] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, wherein the components are AlN, CeO2, YF3, CaF2 and Y2O3, and the particle size is 0.2-3 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of solvent and 0.5-2.5 parts by weight of dispersant are added, and the mixture is put into a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15 mm, and the mixture is processed at a speed of 40-70 r / min for 12-24 hours; then 7-11 parts by weight of binder and 4-8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours, and the ball milled slurry is degassed for 1-2 hours to obtain a tape casting slurry with a viscosity of 5000-10000 mPa.s. The solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol, and butanone. The dispersant is one of castor oil, brown fish oil, polyethylene glycol, and phosphate. The binder is polyvinyl butyral. The plasticizer is one or more of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.
[0063] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3-0.6 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0064] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0065] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0066] (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 60-80°C, 10-40MPa, for 10-30 minutes to obtain a ceramic green sheet.
[0067] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it warm for 3-6 hours to obtain a ceramic debinding sheet.
[0068] (7) Sintering: The ceramic debonding sheet is placed in a high temperature sintering furnace and sintered at 1750-1850° C. for 2-4 hours to obtain a sintered ceramic plate.
[0069] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0070] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0071] The present invention is further described in detail below with multiple embodiments and comparative examples:
[0072] Embodiment 1:
[0073] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0074] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 85%, SiO2 5%, CeO2 5%, and MgO 5%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0075] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 1.2μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 50 parts by weight of solvent and 0.8 parts by weight of dispersant are added to a ball mill equipped with 250 parts by weight of alumina balls with a particle size of 7mm, and the mixture is processed at a speed of 45r / min for 18 hours; then 10 parts by weight of binder and 8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 18 hours to obtain a uniformly mixed granulation slurry. The solvent is ethanol. The dispersant is castor oil. The binder is polyvinyl butyral. The plasticizer is dioctyl phthalate.
[0076] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 80 μm, which is then sieved and batched using a vibrating screen.
[0077] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0078] (4) Isostatic Pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 70°C and 180 MPa for 25 minutes to obtain a ceramic green ceramic structural component.
[0079] (5) Debinding: Place the green ceramic structural part on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 600°C at a heating rate of 0.3°C / min, and keep it at that temperature for 4 hours to obtain a debinding ceramic structural part.
[0080] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1600° C. for 4 hours to obtain a sintered ceramic structure.
[0081] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0082] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 85%, CeO2 2%, YF33%, CaF2 5%, Y2O3 5%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0083] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, wherein the components are AlN, CeO2, YF3, CaF2 and Y2O3, and the particle size is 0.2 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 48 parts by weight of solvent and 0.8 parts by weight of dispersant are added and put into a ball mill equipped with 250 parts by weight of alumina balls with a particle size of 12 mm, and the mixture is processed at a speed of 45 r / min for 18 hours; then 8 parts by weight of binder and 7 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 20 hours. The ball milled slurry is degassed for 1 hour to obtain a casting slurry with a viscosity of 6000 mPa.s. The solvent is ethanol. The dispersant is castor oil. The binder is polyvinyl butyral. The plasticizer is dioctyl phthalate.
[0084] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.5 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0085] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0086] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0087] (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 70°C and 20 MPa for 30 minutes to obtain ceramic green sheets.
[0088] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 480°C at a heating rate of 0.7°C / min, and keep it at this temperature for 5 hours to obtain a ceramic debinding sheet.
[0089] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1780°C for 2 hours to obtain a sintered ceramic plate.
[0090] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0091] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0092] Embodiment 2:
[0093] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0094] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 90%, SiO2 2%, CeO2 4%, and MgO 4%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0095] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 0.2μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45 parts by weight of solvent and 0.5 parts by weight of dispersant are added to a ball mill equipped with 200 parts by weight of alumina balls with a particle size of 5mm, and the mixture is processed at a speed of 40r / min for 16 hours; then 11 parts by weight of binder and 6 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12 hours to obtain a uniformly mixed granulation slurry. The solvent is ethyl acetate. The dispersant is brown fish oil. The binder is polyvinyl butyral. The plasticizer is dimethyl phthalate.
[0096] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 50 μm, which is then sieved and batched using a vibrating screen.
[0097] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0098] (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 60°C and 150MPa for 10 minutes to obtain a ceramic green ceramic structural component.
[0099] (5) Debinding: Place the green ceramic component on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 480°C at a heating rate of 0.7°C / min, and keep it at that temperature for 3 hours to obtain a debinding ceramic component.
[0100] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1500° C. for 2 hours to obtain a sintered ceramic structure.
[0101] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0102] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 90%, CeO2 2%, YF33%, CaF2 3%, Y2O3 2%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0103] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, wherein the components are AlN, CeO2, YF3, CaF2 and Y2O3, and the particle size is 0.8 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45 parts by weight of solvent and 1.3 parts by weight of dispersant are added and put into a ball mill equipped with 200 parts by weight of alumina balls with a particle size of 5 mm, and the mixture is processed at a speed of 50 r / min for 12 hours; then 7 parts by weight of binder and 5 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12 hours. The ball milled slurry is degassed for 1.2 hours to obtain a casting slurry with a viscosity of 5000 mPa.s. The solvent is ethyl acetate. The dispersant is brown fish oil. The binder is polyvinyl butyral. The plasticizer is dimethyl phthalate.
[0104] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0105] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0106] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0107] (5) Lamination: The printed ceramic green sheets are stacked and placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 60°C and 10 MPa for 20 minutes to obtain ceramic green sheets.
[0108] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450°C at a heating rate of 0.4°C / min, and keep it at this temperature for 4 hours to obtain a ceramic debinding sheet.
[0109] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1750° C. for 2.5 hours to obtain a sintered ceramic plate.
[0110] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0111] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0112] Embodiment 3:
[0113] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0114] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 86%, SiO2 4%, CeO2 5%, MgO 5%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0115] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, respectively, with a particle size of 1.6μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 52 parts by weight of solvent and 2.2 parts by weight of dispersant are added to a ball mill equipped with 280 parts by weight of alumina balls with a particle size of 10mm, and the mixture is processed at a speed of 50r / min for 12 hours; then 8 parts by weight of binder and 5 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 16 hours to obtain a uniformly mixed granulation slurry. The solvent is isopropyl alcohol. The dispersant is a phosphate ester. The binder is polyvinyl butyral. The plasticizer is dibutyl phthalate.
[0116] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 90 μm, which is then sieved and batched using a vibrating screen.
[0117] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0118] (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 80°C and 200 MPa for 15 minutes to obtain a ceramic green ceramic structure.
[0119] (5) Debinding: Place the green ceramic structural part on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 500°C at a heating rate of 0.5°C / min, and keep it at that temperature for 5 hours to obtain a debinding ceramic structural part.
[0120] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1580° C. for 3 hours to obtain a sintered ceramic structure.
[0121] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0122] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 86%, CeO2 5%, YF32%, CaF2 3%, Y2O3 4%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0123] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, and the components are AlN, CeO2, YF3, CaF2 and Y2O3, respectively, with a particle size of 1.2 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 50 parts by weight of solvent and 0.5 parts by weight of dispersant are added and put into a ball mill equipped with 280 parts by weight of alumina balls with a particle size of 10 mm, and the mixture is processed at a speed of 60 r / min for 20 hours; then 10 parts by weight of binder and 6 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 18 hours. The ball-milled slurry is degassed for 1.8 hours to obtain a casting slurry with a viscosity of 8000 mPa.s. The solvent is n-butanol. The dispersant is polyethylene glycol. The binder is polyvinyl butyral. The plasticizer is dibutyl phthalate.
[0124] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.6 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0125] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0126] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0127] (5) Lamination: The printed ceramic green sheets are stacked and placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 65°C and 15MPa for 10 minutes to obtain ceramic green sheets.
[0128] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 600°C at a heating rate of 0.5°C / min, and keep it at this temperature for 3 hours to obtain a ceramic debinding sheet.
[0129] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1800° C. for 4 hours to obtain a sintered ceramic plate.
[0130] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0131] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 33, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0132] Embodiment 4:
[0133] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0134] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 87%, SiO2 3%, CeO2 5%, and MgO 5%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0135] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 3μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 55 parts by weight of solvent and 2.5 parts by weight of dispersant are added to a ball mill equipped with 230 parts by weight of alumina balls with a particle size of 15mm, and the mixture is processed at a speed of 55r / min for 22 hours; then 7 parts by weight of binder and 7 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 20 hours to obtain a uniformly mixed granulation slurry. The solvent is n-butanol. The dispersant is a phosphate ester. The binder is polyvinyl butyral. The plasticizer is diisononyl phthalate.
[0136] (2) Granulation: The mixed granulation slurry is formed in a granulation drying tower to obtain granulation powder with a particle size of 100 μm, which is then sieved and batched through a vibrating screen.
[0137] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0138] (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 65°C and 170 MPa for 30 minutes to obtain a ceramic green ceramic structural component.
[0139] (5) Debinding: Place the green ceramic component on a corundum-mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450°C at a heating rate of 0.6°C / min, and keep it at that temperature for 6 hours to obtain a debinding ceramic component.
[0140] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1620° C. for 4 hours to obtain a sintered ceramic structure.
[0141] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0142] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 87%, CeO2 4%, YF35%, CaF2 2%, Y2O3 2%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0143] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, and the components are AlN, CeO2, YF3, CaF2 and Y2O3, respectively, with a particle size of 1.8 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 54 parts by weight of solvent and 2 parts by weight of dispersant are added to a ball mill equipped with 270 parts by weight of alumina balls with a particle size of 14 mm, and the mixture is processed at a speed of 70 r / min for 24 hours; then 9 parts by weight of binder and 4 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 22 hours. The ball-milled slurry is degassed for 1.5 hours to obtain a casting slurry with a viscosity of 9000 mPa.s. The solvent is butanone. The dispersant is a phosphate ester. The binder is polyvinyl butyral. The plasticizer is diisononyl phthalate.
[0144] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.4 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0145] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0146] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0147] (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 75°C and 25MPa for 15 minutes to obtain ceramic green sheets.
[0148] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 650°C at a heating rate of 0.3°C / min, and keep it at this temperature for 6 hours to obtain a ceramic debinding sheet.
[0149] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1850° C. for 3 hours to obtain a sintered ceramic plate.
[0150] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0151] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0152] Embodiment 5:
[0153] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0154] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 88%, SiO2 5%, CeO2 2%, and MgO 5%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0155] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, respectively, with a particle size of 2.2μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 54 parts by weight of solvent and 2.3 parts by weight of dispersant are added to a ball mill equipped with 260 parts by weight of alumina balls with a particle size of 12mm, and the mixture is processed at a speed of 70r / min for 24 hours; then 9 parts by weight of binder and 4 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 24 hours to obtain a uniformly mixed granulation slurry. The solvent is a mixture of ethanol, ethyl acetate and isopropanol. The dispersant is castor oil. The binder is polyvinyl butyral. The plasticizer is a mixture of dioctyl phthalate and dimethyl phthalate.
[0156] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 85 μm, which is then sieved and batched using a vibrating screen.
[0157] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0158] (4) Isostatic Pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 75°C and 190 MPa for 22 minutes to obtain a ceramic green ceramic structural component.
[0159] (5) Debinding: Place the green ceramic component on a corundum-mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 650°C at a heating rate of 0.8°C / min, and keep it at that temperature for 4 hours to obtain a debinding ceramic component.
[0160] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1550° C. for 3 hours to obtain a sintered ceramic structure.
[0161] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0162] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 88%, CeO2 3%, YF33%, CaF2 4%, Y2O3 2%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0163] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, and the components are AlN, CeO2, YF3, CaF2 and Y2O3, respectively, with a particle size of 2.4μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 46 parts by weight of solvent and 2.3 parts by weight of dispersant are added and put into a ball mill equipped with 240 parts by weight of alumina balls with a particle size of 13mm, and the mixture is processed at a speed of 65r / min for 23 hours; then 11 parts by weight of binder and 8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 24 hours. The ball-milled slurry is degassed for 1.7 hours to obtain a casting slurry with a viscosity of 10000mPa.s. The solvent is a mixture of ethanol, ethyl acetate and isopropanol. The dispersant is polyethylene glycol. The binder is polyvinyl butyral. The plasticizer is a mixture of dioctyl phthalate, dimethyl phthalate and dibutyl phthalate.
[0164] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.5 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0165] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0166] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0167] (5) Lamination: The printed ceramic green sheets are stacked and placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 80°C and 30 MPa for 25 minutes to obtain ceramic green sheets.
[0168] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 500°C at a heating rate of 0.8°C / min, and keep it at that temperature for 4 hours to obtain a ceramic debinding sheet.
[0169] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1830° C. for 3.5 hours to obtain a sintered ceramic plate.
[0170] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0171] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0172] Embodiment 6:
[0173] This embodiment discloses a specific structure of a composite electrostatic chuck of aluminum oxide and aluminum nitride, including a metal base 10 , an aluminum oxide ceramic structure 20 , an aluminum nitride ceramic dielectric layer 30 , a heating layer 40 and an adsorption electrode layer 50 .
[0174] The alumina ceramic structure 20 is coated on the outside of the metal base 10, and the alumina ceramic structure 20 includes the following raw materials in weight percentage: Al2O3 88%, SiO2 5%, CeO25%, MgO 2%. Specifically, the preparation method of the alumina ceramic structure 20 includes the following steps:
[0175] (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, and the components are Al2O3, SiO2, CeO2 and MgO, respectively, with a particle size of 2.8μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 48 parts by weight of solvent and 1.4 parts by weight of dispersant are added to a ball mill equipped with 300 parts by weight of alumina balls with a particle size of 9mm, and the mixture is processed at a speed of 65r / min for 20 hours; then 10 parts by weight of binder and 5 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 23 hours to obtain a uniformly mixed granulation slurry. The solvent is a mixture of ethanol, ethyl acetate, isopropanol, n-butanol and butanone. The dispersant is castor oil. The binder is polyvinyl butyral. The plasticizer is a mixture of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate and diisononyl phthalate.
[0176] (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 60 μm, which is then sieved and batched using a vibrating screen.
[0177] (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press and maintain the pressure at 500T for 10 minutes to obtain an alumina blank.
[0178] (4) Isostatic Pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging. The plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 68°C and 160 MPa for 25 minutes to obtain a ceramic green ceramic structure.
[0179] (5) Debinding: Place the green ceramic component on a corundum-mullite support plate, load it into an atmosphere resistance furnace, and slowly heat it to 550°C at a heating rate of 1°C / min, and keep it at that temperature for 5 hours to obtain a debinding ceramic component.
[0180] (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1560° C. for 2 hours to obtain a sintered ceramic structure.
[0181] (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
[0182] The aluminum nitride ceramic dielectric layer 30 includes the following raw materials in weight percentage: AlN 88%, CeO2 4%, YF33%, CaF23%, Y2O3 2%. The aluminum nitride ceramic dielectric layer 30 includes a first dielectric layer 31, a second dielectric layer 32 and a third dielectric layer 33. The first dielectric layer 31 is located at the top of the aluminum nitride ceramic dielectric layer 30, and an adsorption electrode layer 50 is arranged below it for providing adsorption voltage. The second dielectric layer 32 is below the adsorption electrode layer 50 for insulation. The heating layer 40 is located below the second dielectric layer 32 for temperature control during the working process. The third dielectric layer 33 is below the heating layer 40 for insulation shielding and connected to the lower alumina ceramic structure 20. Specifically, the preparation method of the aluminum nitride ceramic dielectric layer 30 includes the following steps:
[0183] (1) Preparation of slurry: The raw materials for preparing aluminum nitride ceramic dielectric layer are mixed in a certain proportion, and the components are AlN, CeO2, YF3, CaF2 and Y2O3, respectively, with a particle size of 3μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 53 parts by weight of solvent and 2.5 parts by weight of dispersant are added to a ball mill equipped with 300 parts by weight of alumina balls with a particle size of 15mm, and the mixture is processed at a speed of 55r / min for 22 hours; then 10 parts by weight of binder and 6 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 19 hours. The ball-milled slurry is degassed for 2 hours to obtain a casting slurry with a viscosity of 8500mPa.s. The solvent is a mixture of ethanol, ethyl acetate, isopropanol, n-butanol and butanone. The dispersant is brown fish oil. The binder is polyvinyl butyral. The plasticizer is a mixture of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate and diisononyl phthalate.
[0184] (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine.
[0185] (3) Punching: Use a laser puncher or a mechanical puncher to process structural holes and positioning hole structures on the ceramic raw tile.
[0186] (4) Printing and filling holes: After punching, the surface of the ceramic green tile is printed with metal slurry and filled with holes using a printing and filling machine; the main components of the metal slurry include tungsten, molybdenum and their alloys, and their main function is to provide a conductive path and generate heat.
[0187] (5) Lamination: The printed ceramic green sheets are stacked and placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press and pressed at 68°C and 40MPa for 22 minutes to obtain ceramic green sheets.
[0188] (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 550°C at a heating rate of 1°C / min, and keep it at this temperature for 5 hours to obtain a ceramic debinding sheet.
[0189] (7) Sintering: The ceramic debonding sheet is placed in a high-temperature sintering furnace and sintered at 1810° C. for 3 hours to obtain a sintered ceramic plate.
[0190] (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
[0191] In addition, the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20 are welded by high-temperature solder to improve reliability. Specifically, the third dielectric layer 33 is combined with the alumina ceramic structural member 20 by high-temperature welding, and a plurality of helium holes 301 are opened on the surface periphery of the first dielectric layer 31, and the plurality of helium holes 301 are arranged in a circle at intervals, and each helium hole 301 penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer 30 and the alumina ceramic structural member 20. In addition, the heating layer 40 is connected to a first lead-out terminal 41, and the first lead-out terminal 41 passes through the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10, and the adsorption electrode layer 50 is connected to a second lead-out terminal 51, and the second lead-out terminal 51 passes through the second dielectric layer 32, the heating layer 40, the third dielectric layer 33, the alumina ceramic structural member 20 and the metal base 10 to expose the bottom surface of the metal base 10.
[0192] Comparative Example 1:
[0193] Aluminum nitride electrostatic chuck is a conventional electrostatic chuck without ceramic structural parts.
[0194] Comparative Example 2:
[0195] Alumina electrostatic chuck is a conventional structure electrostatic chuck without ceramic structural parts.
[0196] The conventional methods are used to perform various performance tests on the electrostatic chucks of the above-mentioned embodiments and comparative examples. The test results are shown in the following table.
[0197]
[0198] Conclusion: The composite electrostatic chuck uses aluminum nitride as the ceramic dielectric layer. The aluminum nitride ceramic dielectric layer has excellent thermal conductivity and temperature uniformity, and its insulation performance is good, so that the composite electrostatic chuck can effectively control the temperature during the semiconductor processing process and ensure the temperature uniformity of the wafer surface; at the same time, the metal base is covered with an alumina ceramic structural member, which is resistant to high temperature, corrosion and wear; the composite electrostatic chuck has excellent thermal conductivity and excellent dielectric properties, and its insulation performance is good, so that the composite electrostatic chuck has good electrical insulation performance, and can also shield the plasma from erosion of the metal base, and does not produce particulate pollutants to contaminate the wafer. Among Examples 1-6, the thermal conductivity, volume density, flexural strength, thermal shock, volume resistance, 0.1mm particle number and temperature uniformity of Example 4 are the best, and the electrostatic chuck can be used in high-power and high-plasma density scenarios.
[0199] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A composite electrostatic chuck of aluminum oxide and aluminum nitride, characterized in that: The invention comprises a metal base, an alumina ceramic structure, an aluminum nitride ceramic dielectric layer, a heating layer and an adsorption electrode layer; the alumina ceramic structure is coated on the outside of the metal base, and the alumina ceramic structure comprises the following raw materials in weight percentage: Al2O3 85-90%, SiO2 2-5%, CeO2 2-5%, MgO 2-5%; the aluminum nitride ceramic dielectric layer comprises the following raw materials in weight percentage: AlN 85-90%, CeO2 2-5%, YF32-5%, CaF2 2-5%, Y2O3 2-5%, the aluminum nitride ceramic dielectric layer includes a first dielectric layer, a second dielectric layer and a third dielectric layer, the first dielectric layer is located at the top of the aluminum nitride ceramic dielectric layer, an adsorption electrode layer is arranged below it for providing adsorption voltage, and a second dielectric layer is arranged below the adsorption electrode layer for insulation, the heating layer is located below the second dielectric layer for temperature control of the working process, and the third dielectric layer is arranged below the heating layer for insulation shielding and connected to the lower alumina ceramic structural member.
2. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 1, characterized in that: The method for preparing the aluminum nitride ceramic dielectric layer comprises the following steps: (1) Preparation of slurry: The raw materials for preparing the aluminum nitride ceramic dielectric layer are mixed in a certain proportion, wherein the components are AlN, CeO2, YF3, CaF2 and Y2O3, and the particle size is 0.2-3 μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of a solvent and 0.5-2.5 parts by weight of a dispersant are added, and the mixture is put into a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15 mm, and the mixture is processed at a speed of 40-70 r / min for 12-24 hours; then 7-11 parts by weight of a binder and 4-8 parts by weight of a plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours. The ball-milled slurry is degassed for 1-2 hours to obtain a tape casting slurry with a viscosity of 5000-10000 mPa.s; (2) Tape casting and cutting: The degassed tape slurry is formed using a tape casting machine to obtain a ceramic green tape with a thickness of 0.3-0.6 mm, which is then cut into ceramic green sheets of uniform size using a cutting machine; (3) Punching: Use a laser punch or mechanical punch to process structural holes and positioning hole structures on the ceramic green tile; (4) Printing and filling holes: The surface of the ceramic green tile after punching is printed with metal slurry and filled with holes using a printing and filling machine; (5) Lamination: The printed ceramic green sheets are stacked, placed on a rigid pad, put into a plastic bag for vacuum sealing, and then the sealed stacked sheets are placed in an isostatic press for 10-30 minutes at 60-80° C. and 10-40 MPa to obtain a ceramic green sheet; (6) Debinding: Place the green ceramic plate on a corundum mullite support plate, put it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it warm for 3-6 hours to obtain a ceramic debinding sheet; (7) Sintering: The ceramic debonding sheet is placed in a high temperature sintering furnace and sintered at 1750-1850° C. for 2-4 hours to obtain a sintered ceramic plate; (8) Machining: The sintered ceramic plate is subjected to final processing by double-sided grinding and machining equipment to obtain an aluminum nitride ceramic dielectric layer with a flatness of less than 5 μm and a surface roughness of less than 0.1 μm.
3. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 2, characterized in that: The metal paste mainly comprises tungsten, molybdenum and their alloys, and its main functions are to provide a conductive path and generate heat.
4. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 1, characterized in that: The method for preparing the alumina ceramic structural component comprises the following steps: (1) Preparation of slurry: The raw materials for preparing alumina ceramic structural parts are mixed in a certain proportion, wherein the components are Al2O3, SiO2, CeO2 and MgO, and the particle size is 0.2-3μm. The raw materials are accurately weighed in a certain proportion, and based on the mass of the powder, 45-55 parts by weight of solvent and 0.5-2.5 parts by weight of dispersant are added, and the mixture is put into a ball mill equipped with 200-300 parts by weight of alumina balls with a particle size of 5-15mm, and processed at a speed of 40-70r / min for 12-24 hours; then 7-11 parts by weight of binder and 4-8 parts by weight of plasticizer are added to the ball mill, and the ball milling is continued for 12-24 hours to obtain a uniformly mixed granulation slurry; (2) Granulation: The mixed granulation slurry is formed using a granulation drying tower to obtain granulation powder with a particle size of 50-100 μm, which is then sieved and batched using a vibrating screen; (3) Dry pressing: Pour the granulated powder into a metal mold using a hydraulic press, and maintain the pressure at 500T for 10 minutes to obtain an alumina blank; (4) Isostatic pressing: The dry-pressed alumina blank is subjected to vacuum packaging treatment using a vacuum packaging machine, and then placed on a rigid pad and put into a plastic bag for vacuum packaging; the plastic-sealed stacked sheets are then placed in an isostatic press and pressed at 60-80° C. and 150-200 MPa for 10-30 minutes to obtain a ceramic green ceramic structural part; (5) Debinding: Place the green ceramic structural part on a corundum mullite support plate, load it into an atmosphere resistance furnace, slowly heat it to 450-650°C at a heating rate of 0.3-1°C / min, and keep it at this temperature for 3-6 hours to obtain a debinding ceramic structural part; (6) Sintering: The debinding ceramic structure is placed in a high-temperature sintering furnace and sintered at 1500-1650° C. for 2-4 hours to obtain a sintered ceramic structure; (7) Machining: The sintered ceramic structural parts are finally processed by double-sided grinding and machining equipment to obtain alumina ceramic structural parts with a flatness of less than 5um and a surface roughness of less than 0.1um.
5. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 4, characterized in that: The solvent is one or more of ethanol, ethyl acetate, isopropanol, n-butanol and butanone.
6. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 4, characterized in that: The dispersant is one of castor oil, brown fish oil, polyethylene glycol and phosphate ester.
7. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 4, characterized in that: The binder is polyvinyl butyral.
8. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 4, characterized in that: The plasticizer is one or more of dioctyl phthalate, dimethyl phthalate, dibutyl phthalate, and diisononyl phthalate.
9. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 1, characterized in that: The aluminum nitride ceramic dielectric layer and the aluminum oxide ceramic structural member are welded by high-temperature solder to improve reliability.
10. The composite electrostatic chuck of aluminum oxide and aluminum nitride according to claim 1, characterized in that: The third dielectric layer is combined with the alumina ceramic structural component by high-temperature welding. A plurality of helium holes are opened on the periphery of the surface of the first dielectric layer. The plurality of helium holes are arranged in a circle at intervals. Each helium hole penetrates the upper and lower surfaces of the aluminum nitride ceramic dielectric layer and the alumina ceramic structural component.
Citation Information
Patent Citations
Electrostatic chuck
CN103201235A
Electrostatic chuck of non-sintered aluminum nitride
CN110957254A
Semiconductor process equipment and electrostatic chuck assembly thereof
CN112582330A
Manufacturing method of electrostatic chuck
CN118324537A
Alumina-based composite ceramic dielectric layer and preparation method thereof
CN118619697A
Cited By
Silicon carbide electrostatic chuck based on tape casting and preparation method thereof
CN121318460A